Prognostic implications of ST‐segment elevation in lead aVR in patients with acute coronary syndrome: A meta‐analysis. Issue 1 (15th October 2020) - Wang, Aqian; Singh, Vikas; Duan, Yichao; Su, Xin; Su, Hongling; Zhang, Min; Cao, Yunshan
Abstract: Background: ST‐segment elevation (STE) in lead aVR is a useful tool in recognizing patients with left main or left anterior descending coronary obstruction during acute coronary syndrome (ACS). The prognostic implication of STE in lead aVR on outcomes has not been established. Methods: We performed a systematic search for clinical studies about STE in lead aVR in four databases including PubMed, EMBASE, Cochrane Library, and Web of Science. Primary outcome was in‐hospital mortality. Secondary outcomes included in‐hospital (re)infarction, in‐hospital heart failure, and 90‐day mortality. Results: We included 7 studies with a total of 7, 700 patients. The all‐cause in‐hospital mortality of patients with STE in lead aVR during ACS was significantly higher than that of patients without STE (OR: 4.37, 95% CI 1.63 to 11.68, p = .003). Patients with greater STE (>0.1 mV) in lead aVR had a higher in‐hospital mortality when compared to lower STE (0.05–0.1 mV) (OR: 2.00, 95% CI 1.11–3.60, p = .02), However, STE in aVR was not independently associated with in‐hospital mortality in ACS patients (OR: 2.72, 95% CI 0.85–8.63, p = .09). The incidence of in‐hospital myocardial (re)infarction (OR: 2.77, 95% CI 1.30–5.94, p = .009), in‐hospital heart failure (OR: 2.62, 95% CI 1.06–6.50, p = .04), and 90‐day mortality (OR: 10.19, 95% CI 5.27–19.71, p < .00001) was also noted to be higher in patients STE in lead aVR. Conclusions: This contemporary meta‐analysis shows STE in lead aVR is a poor prognostic marker in patients with ACS with higher in‐hospital mortality, reinfarction, heart failure and 90‐day mortality. Greater magnitude of STE portends worse prognosis. Further studies are needed to establish an independent predictive role of STE in aVR for these adverse outcomes.